Pemanfaatan Metode One Week One Story Dalam Meningkatkan Kemampuan Komunikasi Anak di TK Al-Qur’an - Alimah, Alimah; Aryani, Nini; Herwina, Herwina (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2026)
This study aims to describe the effectiveness of the "One Week One Story" program in enhancing the communication skills of Group A children at TK Al-Qur’an, Anambas Regency. The research employed Classroom Action Research (CAR) conducted over two cycles. The subjects of this study were 9 students, consisting of 4 boys and 5 girls. Data were collected through systematic observation and documentation, then analyzed using descriptive qualitative and quantitative methods. The results indicated a significant improvement in children's communication skills at each stage. In the pre-cycle stage, communication skills were distributed between the "Poor" category (21% - 40%) for 4 children and the "Fair" category (41% - 60%) for 5 children. Following the intervention in Cycle I, student performance improved, with 3 children reaching the "Fair" category (41% - 60%) and 6 children achieving the "Good" category (61% - 80%). The progress culminated in Cycle II, where a substantial increase was observed: 3 children remained in the "Good" category (61% - 80%), while 6 children reached the "Excellent" interval (81% - 100%). Based on these findings, it can be concluded that the consistent implementation of the "One Week One Story" program is effective in optimizing communication skills in early childhood.